2020
DOI: 10.1139/as-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing indicators as boundary objects in integrating Inuit knowledge and western science for marine resource management

Abstract: A complex co-management system exists across Inuit Nunangat, whereby federal, provincial, territorial governments and Inuit organizations manage natural resources cooperatively. Under Inuit land claim agreements, Inuit Knowledge, western science, and co-produced knowledge are to be used side by side to support decision-making. However, the mechanisms of effectively integrating these knowledge systems to inform decision makers remain poorly understood. This limits Inuit self-determination, hinders knowledge pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 106 publications
0
31
0
Order By: Relevance
“…For example, Schuttenberg and Guth (2015) found that social-ecological context represented a component of co-productive capacities that increased the salience of knowledge for a climate change action plan in Hawaii. Knowledge co-production in northern Canada often centered on fostering contextual benefits for Indigenous communities and ILK, such as reversing colonial research legacies and lack of agency in Arctic communities, promoting ecosystem health, and institutional adaptations to climate change (Carter et al 2019;Falardeau et al 2019;Kourantidou et al 2020;Mantyka-Pringle et al 2017; Schott et al 2020; Vogel and Bullock 2020). Indeed, equitable recognition and interactions with contextual ILK emerged as a common theme in this review, contrasting with findings that climate adaptation scholars tended to study ILK in co-production as fixed data rather than contextual relationships (Klenk et al 2017).…”
Section: Guiding Principles Of Knowledge Co-productionmentioning
confidence: 99%
“…For example, Schuttenberg and Guth (2015) found that social-ecological context represented a component of co-productive capacities that increased the salience of knowledge for a climate change action plan in Hawaii. Knowledge co-production in northern Canada often centered on fostering contextual benefits for Indigenous communities and ILK, such as reversing colonial research legacies and lack of agency in Arctic communities, promoting ecosystem health, and institutional adaptations to climate change (Carter et al 2019;Falardeau et al 2019;Kourantidou et al 2020;Mantyka-Pringle et al 2017; Schott et al 2020; Vogel and Bullock 2020). Indeed, equitable recognition and interactions with contextual ILK emerged as a common theme in this review, contrasting with findings that climate adaptation scholars tended to study ILK in co-production as fixed data rather than contextual relationships (Klenk et al 2017).…”
Section: Guiding Principles Of Knowledge Co-productionmentioning
confidence: 99%
“…In addition to the Fisheries Act, several other federal government mandates put emphasis on inclusion of IK for guiding and informing science and management. These mandates cover both commercial and subsistence harvesting of marine resources, and, while there are stronger voices and literature that support the need to include and prioritize IK for subsistence harvest (Kourantidou et al, 2020), such is not the case for commercial fisheries. This is true despite strong evidence that ignoring IK can be detrimental for the conservation of stocks [e.g., see Milich (1999) for an example of undervaluation of IK in the Newfoundland (François) cod fishery].…”
Section: Household Income By Quintilesmentioning
confidence: 99%
“…The cod fishery collapse in Newfoundland and Labrador has also undermined trust on behalf of fishers in top-down management approaches given past failures to predict stocks (Schott, 2004). Past colonial practices in resource governance in Nunatsiavut and all across Inuit Nunangat (Felt et al, 2012;Keenan et al, 2018;Kourantidou et al, 2020) perpetuate mistrust and create barriers to fruitful partnerships between local users and resource managers which may come at the cost of mismanaging the fishery.…”
Section: Household Income By Quintilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to combine the scientific and educational values of IQ and Western science have been initiated and implemented in the eastern Canadian Arctic and their value demonstrated. These include marine resource management programs (Alexander et al, 2019;Kourantidou et al, 2020), cooperative projects of the Canadian High Arctic Research Station in Cambridge Bay (Burke, 2019), inclusion of IQ knowledge about Arctic climate change at the National Snow and Ice Data Center (Weatherhead et al, 2010), and SmartICE, which, in collaboration with the Nunatsiavut government, integrates traditional knowledge about the ice with real-time data gathered from sensors embedded in sea ice (Halliday, 2020).…”
Section: Introductionmentioning
confidence: 99%